Amazonite : mineralogy, crystal chemistry, and typomorphism - Ostroumov, M. N. (Mikhail Nikolaevich) (Elsevier, 2016)
Amazonite: Mineralogy, Crystal Chemistry and Typomorphism provides in-depth coverage of the geological setting, mineralogy, chemistry,spectroscopic parameters, typomorphic features, and potential technological and economical uses associated with amazonite discovery. Featuring detailed characterization of the geological settings of amazonite, as well a full investigation of its chemical composition, structural features, and properties with respect to each genetic type of granite, this essential reference covers all key aspects of amazonite and the benefits of its discovery. Both newcomers and seasoned professionals in the field of mineralogy worldwide will find this translation of the popular Russian text a welcome addition to the literature on amazonite.